2016
DOI: 10.4025/actascitechnol.v38i4.28788
|View full text |Cite
|
Sign up to set email alerts
|

<b>Vitamin C supplementation on growth performance and gonadal development in Nile tilapia

Abstract: ABSTRACT. The study aimed to verify the vitamin C supplementation on performance and gonadal development of Nile tilapia. 160 fingerlings distributed in 16 tanks with 65 L capacity and constant water renewal in a closed recirculation system were used. The design was completely randomized with four treatments (0, 150, 300, and 600 mg of monophosphate L-ascorbic acid kg -1 diet) and four replications. We evaluated the weight gain parameters, apparent feed conversion, apparent feed intake and carcass yield to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…There was a significant difference (P<0.05) in carcass yield (CY) among experimental groups. In agreement with Martins et al (2016). The 60 mg ascorbic acid kg-1 diet found as requirement level for maximum growth agrees with Li and Lovell (1985) who demonstrated that fish rose from 3 to 19g required 60 mg ascorbic acid kg-1 diet for maximum weight gain.…”
Section: Table (3)supporting
confidence: 89%
See 1 more Smart Citation
“…There was a significant difference (P<0.05) in carcass yield (CY) among experimental groups. In agreement with Martins et al (2016). The 60 mg ascorbic acid kg-1 diet found as requirement level for maximum growth agrees with Li and Lovell (1985) who demonstrated that fish rose from 3 to 19g required 60 mg ascorbic acid kg-1 diet for maximum weight gain.…”
Section: Table (3)supporting
confidence: 89%
“…There was a significant difference (P<0.05) between experimental groups (Table ) in GW. The highest GW was recorded in T5, T4, and T3 and the lowest value of GW in T1, In agreement with Martins et al (2016).…”
Section: Table (3)supporting
confidence: 86%
“…Each aquarium was considered an experimental unit, totaling 12 experimental units. The experiment was carried out according to Martins et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The research was carried out according to Martins et al (2016) number ethics committee for animal use 43079/2012.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Other vitamins, like vitamin C, E an Zn mineral on the Nile tilapia (O. niloticus) ration might improve spawning frequency, larvae productions, fecundity, hatching rate, sperm motility and viability ( Gamanpilla et al, 2007). During the study of reproductive performance, vitamin C (AA) supplemetned at a dosage of 150 mg kg-1 on the O.niloticus fed ration incrase the Gonado Somato Indeks (GSI) (Martins et al, 2016). Gonad maturity is related to egg development.…”
Section: Introductionmentioning
confidence: 99%